(untitled) (Research, Society and Development, 2021)
Feeding is responsible for the higher cost of animal production, restricting the profit margin of breeders. The use of co-products in food is vital not only to make animal production viable, but also to mitigate environmental pollution and make animal feed available in non-grain producing regions. The aim of this study was to evaluate the nutritional potential of the co-product of the diet used in the creation of Diatraea saccharalis in animal feed. The experimental design was completely randomized with two treatments and six replications, consisting of the diet and leftovers from the diet of D. saccharalis. The samples were homogenized, ground and analyzed for percentages of dry matter, moisture, crude protein, ether extract, crude fiber and mineral matter. Gross energy (kcal/kg) was determined in a Parr-type calorimetric pump. Data were subjected to analysis of variance; means were compared by the F test (P < 0.05). There was a significant effect (P<0.05) for most variables, except for crude protein and ethereal stratum. The percentage of dry matter in the residue was lower compared to the percentage of dry matter in the diet. Changes in dry matter occur due to the increase in residue moisture. The crude protein values ​​in the natural matter of the samples were similar to the corn protein values and well below the (protein) value of soybean meal, indicating that these ingredients do not replace soybean meal in animal diets. The residue from the diet used in the creation of D. saccharalis has potential for use in animal diets after drying.